(untitled) (Global Journal of Management and Business Research, 2017)
This paper investigated the impact of foreign exchange volatility on foreign direct investment in Nigeria from 1999- to 2016. The research design adopted in this research is the ex-post facto research design involving the collation of relevant data from statistical bulletins in respect of the variables in the study. Ordinary least squares were used to estimate the partial coefficients of the independent variables. The findings of this study suggest that fluctuations in exchange rate have a positive and significant impact on foreign private investment in Nigeria. This may be attributed to the competitive levels of the Nigerian foreign exchange market, leading to the avoidance of excessive volatility. The result indicates that exchange rate fluctuations has positive and significant impact on Nigeria’s foreign private investment which supports the argument that FDI investment in Nigeria is determined by exchange rate as well as technology, entrepreneurial skills, source of capital an overall.